If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying t = 3t + 1 Reorder the terms: t = 1 + 3t Solving t = 1 + 3t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-3t' to each side of the equation. t + -3t = 1 + 3t + -3t Combine like terms: t + -3t = -2t -2t = 1 + 3t + -3t Combine like terms: 3t + -3t = 0 -2t = 1 + 0 -2t = 1 Divide each side by '-2'. t = -0.5 Simplifying t = -0.5
| a^2+a-1=0 | | 2(8x-2)=6 | | 9x-3-6x=12 | | -5-9n+6= | | -3(7p+6)-2(5-20p)=3(9+6p) | | c^2=a^2+b^2 | | (n+4)*9=54 | | (n-9)*5=40 | | 13x=8x+40 | | 7(t-5)+7t=7(2t+3)-11 | | 6x=4x+10 | | 3(3x-4)=12 | | -6x^4-4x^2+2=0 | | 18+1.50n=34.50 | | (z+1)(z-12)=11(z-3) | | x^2+36-12x=0 | | 11-3x^2+7x-4=8x+1 | | 3(f+11)=-7.5-6f | | .5x-5+.5x-10=10 | | 144x^4+1152x^2-6912=0 | | 3.59-4.2=4.7a | | 4(y+3)=30 | | 5x^2+4=60 | | -3x+5=-25 | | -4+10y+12=4(2y-4)-6 | | 5x^2+4-60=0 | | 2t+9-11t+33+28=0 | | 4-6x=-44 | | p+3-5=6p-10p | | 21+16x-6x-12=109 | | 3x-2=4x+5 | | 10x^2+21x-10= |